Efficacy of Galcanezumab for Migraine Prevention in Patients With a Medical History of Anxiety and/or Depression: A Post Hoc Analysis of the Phase 3, Randomized, Double‐Blind, Placebo‐Controlled REGAIN, and Pooled EVOLVE‐1 and EVOLVE‐2 Studies - Smitherman, Todd A.; Tietjen, Gretchen E.; Schuh, Kory; Skljarevski, Vladimir; Lipsius, Sarah; D’Souza, Deborah N.; Pearlman, Eric M. (Headache, 2020)
Objective This post hoc analysis evaluated the efficacy of galcanezumab for the prevention of migraine in patients with and without comorbid anxiety and/or depression. Background Patients with migraine have a higher risk of anxiety and/or depression. Given the high prevalence of psychiatric symptoms and their potential negative prognostic impact, determining the efficacy of migraine treatments in patients with these comorbidities is important. Methods The results of 2 phase 3 episodic migraine studies of patients with 4‐14 migraine headache days (MHD) per month were pooled. A third chronic migraine study, which was evaluated separately, enrolled patients with ≥15 headache days per month, of which ≥8 had migraine‐like features. Patients in all 3 studies were randomized 2:1:1 to placebo, galcanezumab 120 mg, or galcanezumab 240 mg. The efficacy of galcanezumab on migraine was measured in subgroups of patients with anxiety and/or depression (current or past) and patients without. A repeated measures model was used to compare treatment groups within each subgroup and to test for consistency of treatment effect across the anxiety/depression subgroups (subgroup‐by‐treatment interaction) during the double‐blind treatment phases. Results Among 1773 intent‐to‐treat patients with episodic migraine, both doses of galcanezumab demonstrated statistically significant improvements relative to placebo in overall number of MHD for the subgroups of patients with anxiety and/or depression (mean change difference from placebo [95% CI]: −2.07 [−2.81, −1.33] for galcanezumab 120 mg [P < .001], −1.91 [−2.78, −1.04] for 240 mg [P < .001]) and without anxiety and/or depression (mean change difference from placebo [95% CI]: −1.92 [−2.36, −1.47] for 120 mg [P < .001], −1.77 [−2.20, −1.33] for 240 mg [P < .001]), as was observed for the secondary outcomes of MHD with acute medication use and functional impairment. Among 1113 intent‐to‐treat patients with chronic migraine, those with anxiety and/or depression had significant reductions in overall MHD frequency with the 240‐mg dose (mean change difference from placebo [95% CI]: −1.92 [−3.52, −0.33]; P = .018), whereas significant reductions were observed at both the 120‐mg (mean change difference from placebo [95% CI]: −2.29 [−3.26, −1.31]; P < .001) and 240‐mg (−1.85 [−2.83, −0.87]; P < .001) doses in patients without anxiety and/or depressions. Significant reductions (P < .01) in MHD with acute medication use were observed at both doses within both anxiety/depression subgroups and for overall functional impairment for patients without anxiety and/or depression, though neither dose significantly reduced overall functional impairment beyond placebo in the subgroup with anxiety and/or depression. In the episodic and chronic migraine studies, the subgroup‐by‐treatment interaction was not statistically significant for MHD, MHD with acute medication use, or functional impairment (chronic study only), suggesting a lack of evidence of differential effect between subgroups. Furthermore, differences between subgroups in the mean change differences from placebo, as well as overlapping 95% confidence intervals for the subgroups, indicated lack of a clinical or statistical difference between subgroups for these outcome variables. There was a significantly higher percentage of patients with episodic migraine attaining ≥50%, ≥75%, and 100% reductions, and a higher percentage of patients with chronic migraine attaining ≥50% and ≥75% reductions from baseline with galcanezumab compared with placebo, regardless of medical history of anxiety and/or depression. Conclusions A medical history of anxiety and/or depression does not seem to interfere with response to galcanezumab among patients with episodic migraine, and both doses of galcanezumab appear efficacious for these individuals regardless of this psychiatric history. Among patients with chronic migraine and comorbid anxiety and/or depression, the 240‐mg dose, but not the 120‐mg dose, significantly decreased overall MHD, but neither dose resulted in significantly greater functional improvement. Patients with migraine and comorbid anxiety and/or depression often require additional interventions, and this may be more important in chronic migraine.